2015
DOI: 10.1038/nprot.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of active proteases in fresh-frozen tissues by topical application of quenched activity-based probes

Abstract: Active enzymes, such as proteases, often serve as valuable biomarkers for various disease pathologies. Therefore, methods to detect specific enzyme activities in biological samples can provide information to guide disease detection and diagnosis and to increase our understanding of the biological roles of specific enzyme targets. In this protocol, we outline methods for the topical application of fluorescently quenched activity-based probes (qABPs) to fresh-frozen tissue samples. This technique enables rapid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…To provide evidence for the specificity of B24P, skin biopsies were pretreated with aprotinin and AEBSF that effectively inhibit activity of serine proteases (Figure ). It should be mentioned that these controls should always run in parallel with the experiments as also suggested and performed previously, especially in this case that the B24P does not have a proteolytic enzyme‐selective “bait” and its specificity merits further characterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide evidence for the specificity of B24P, skin biopsies were pretreated with aprotinin and AEBSF that effectively inhibit activity of serine proteases (Figure ). It should be mentioned that these controls should always run in parallel with the experiments as also suggested and performed previously, especially in this case that the B24P does not have a proteolytic enzyme‐selective “bait” and its specificity merits further characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Activity‐based probes have a well‐recognized ability to visualize proteases in vivo . Here, we showed that activography provides similar spatial and semiquantitative information as the in situ zymography method but is advantageous in that activography allows the mapping of enzyme specificities thus opening possibilities for new applications in clinical diagnostic laboratories.…”
Section: Discussionmentioning
confidence: 95%
“…antibody of interest as described previously (34). Briefly, the fresh carotid tissue was frozen in optimal-cutting-temperature compound before sectioning.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…To date, quenched activity probe-based live cell fluorescence imaging has been described for a handful of proteases, such as cysteine cathepsins . The quenched fluorescent activity probes were applied for labeling of active proteases in fresh-frozen cancer tissues (Withana et al, 2016), for macrophage detection in atherosclerotic plaques (Abd-Elrahman et al, 2016), and as a diagnostic tool to image skin tumor margins (Liu et al, 2019). Recently, a small-molecule chemical toolbox was constructed for parallel imaging of human neutrophil serine proteases (NSPs).…”
Section: Introductionmentioning
confidence: 99%